Dental pulp reaction before the presence of decays and dental treatments - Velásquez Reyes, Víctor (2010)
This article reviews the different reactions of the dental pulp before the injuries caused by dental caries and by the different restoration treatments performed on it. Therefore, it was concluded that the main objective is to provide the general practice dentist with the pertinent knowledge to orient, prevent and maintain the dental pulp health.